Komposit Grafit-Polistirena Diperkuat Poliuretan sebagai Penyerap Gelombang Akustik : Fabrication of Polyurethane Composite Foam with Graphite-Polystyrene Filler for Improved Sound Absorption - Adhi Satriyatama; Haris Amaldi; M. Maulana Ibrahim; Aditianto Ramelan (Badan Kerja Sama Pendidikan Metalurgi dan Material (BKPMM), 2019)
Noise, harshness, and vibration (NHV) are problems encountered when driving a vehicle. This can cause serious problems for drivers if exposed to NHV for a long time. In order to avoid the NHV, vehicle are equipped with acoustic tile which functions to absorb vibration from the sound wave and reduce the noise caused by the vehicle’s engine. Polyurethane foam is commonly used as a sound absorption material because of its high sound absorption efficiency. The study aimed at investigating polystyrene (PS) and graphite (G) fillers with polyurethane matrix for improving acoustic property. The research started with optimization of composite that characterized using sound absorption intensity parameters at frequencies of 50 Hz-6000 Hz, and the optimum results obtained at matrix/filler 92.8%wt. The composite morphology is analyzed using SEM-EDX, optical microscopy, and the density. Mechanical test is conducted using Universal Testing Machine (UTM) and achieved the optimum compressive strength at 60G/40PS with 0.65 MPa. The absorption of acoustic waves property was tested in the frequency range 50 Hz-6300 Hz using an impedance tube and obtained the optimum composition at 0G/100PS.